Production and Characterization of Microwave-Activated Palm Kernel Shell (Elaeis Guineensis Jacq.) Activated Charcoal - Lina Lestari; Sapto Raharjo; I Nyoman Sudiana; La Ode Rusman; Siti Manikam (Journal of World Science, 2024)
Research has been conducted on the production and characterization of activated charcoal of palm kernel shells (Elaeis Guineensis Jacq.) by microwave. This study aims to determine the efficiency of charcoal production and its quality after microwave activation so that the test results can provide information that palm kernel shells can be utilized as raw material for making briquettes as an alternative fuel. The experimental stages include drying of palm kernel shells, carbonization with a carbonization reactor, grinding, sieving with 70 mesh and 80 mesh sieves in stages, and activation with microwave. Charcoal characterization includes moisture content, ash content, volatile matter, fixed carbon, and calorific value. The results showed that the production efficiency of the carbonization reactor was 62.2%, the charcoal formation rate was 4.4444 kg/hour, and the material requirement rate was 7.1429 kg/hour. Charcoal can be activated by microwave at 150 watts for 2 minutes, 3 minutes, and 4 minutes. Activated charcoal decreased in moisture content from 5.900% to 4.4834%, decreased volatile matter from 19.1357% to 14.4250%, and increased ash content from 6.1234% to 7.5697%. Fix carbon increased from 68.8409% to 73.5219%, and the calorific value of charcoal increased significantly from 5400.00 cal/gr to 7532.27 cal/gr. It can be concluded that microwave-activated charcoal meets the quality requirements as an ingredient for making briquettes as an alternative fuel. The implication of this research is the new finding that microwaved-activated palm kernel shell charcoal has potential as a briquette-making material with better quality than charcoal without activation.